2017
DOI: 10.1038/ncomms14155
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of cardiac cholinergic neurons enhances susceptibility to ventricular arrhythmias

Abstract: The parasympathetic nervous system plays an important role in the pathophysiology of atrial fibrillation. Catheter ablation, a minimally invasive procedure deactivating abnormal firing cardiac tissue, is increasingly becoming the therapy of choice for atrial fibrillation. This is inevitably associated with the obliteration of cardiac cholinergic neurons. However, the impact on ventricular electrophysiology is unclear. Here we show that cardiac cholinergic neurons modulate ventricular electrophysiology. Mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 68 publications
2
70
0
Order By: Relevance
“…Several lines of clinical evidence show that the addition of GP ablation to pulmonary vein isolation confers a significantly higher success rate compared with pulmonary vein isolation only in patients with atrial fibrillation . However, GP ablation, which destroys the intrinsic cardiac autonomic nervous system, may potentially have impacts on ventricular electrophysiology and arrhythmogenesis . Previous studies by He et al showed that GP stimulation significantly decreased the incidence of ventricular arrhythmias (VA) in a canine model of acute myocardial ischemia, whereas GP ablation had the opposite effect .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of clinical evidence show that the addition of GP ablation to pulmonary vein isolation confers a significantly higher success rate compared with pulmonary vein isolation only in patients with atrial fibrillation . However, GP ablation, which destroys the intrinsic cardiac autonomic nervous system, may potentially have impacts on ventricular electrophysiology and arrhythmogenesis . Previous studies by He et al showed that GP stimulation significantly decreased the incidence of ventricular arrhythmias (VA) in a canine model of acute myocardial ischemia, whereas GP ablation had the opposite effect .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, GP ablation, which destroys the intrinsic cardiac autonomic nervous system, may potentially have impacts on ventricular electrophysiology and arrhythmogenesis. 6 Previous studies by He et al 7,8 showed that GP stimulation significantly decreased the incidence of ventricular arrhythmias (VA) in a canine model of acute myocardial ischemia, whereas GP ablation had the opposite effect. 9 However, the long-term effect of GP ablation on ventricular electrophysiology in a canine postmyocardial infarction (MI) model is still unknown.…”
mentioning
confidence: 99%
“…Furthermore, our results above suggested that the neurodegeneration and apoptosis may be due to the upregulation of AVP. In addition, a recent study reported that disruption of cardiac cholinergic neurons enhances susceptibility to ventricular arrhythmias [33]. Accordingly, we speculated that AVP may exert a destructive role in heart neurons.…”
Section: Discussionmentioning
confidence: 88%
“…For histological studies, cross-sections of murine hearts were stained using H&E staining. Furthermore, specific proteins were detected by immunofluorescent staining of cross-sections or cardiac cells as described previously (64). Staining was carried out according to the detailed protocol described in SI Appendix.…”
Section: Methodsmentioning
confidence: 99%